Auctoritas (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The following article seeks to clarify, taking into account Hobbes’s Leviathan, the conceptual traits of what could be one of the most elusive topics of political theory: authority. It starts from the turn that Hobbes’s gives to this concept by approaching it from authorization and not from authority itself. Besides making explicit the nominalism that founds both the concept of authority and authorization, and the Hobbesian destruction of the notion of “charisma”, the article defends the thesis that the difference between authority and dominion is only possible in Hobbes’s philosophy by a stylized rational construct that clearly outlines what Hans Kelsen four centuries later will call “legal fiction”. In this way this text seeks to highlight the tension between command as an undeniable historical fact and authority as rational garment that not only justifies it but makes it possible.